2020
DOI: 10.1111/maec.12591
|View full text |Cite
|
Sign up to set email alerts
|

Response of the bacterioplankton composition to inorganic nutrient loading and phytoplankton in southern Korean coastal waters: A mesocosm study

Abstract: In Korean coastal waters (KCW), nutrient loading from the four major rivers usually peaks in summer, probably due to the large amount of water discharge in rainy seasons, but little is known about the responses of the bacterial community composition to inorganic nutrient loading. To gain deeper understanding of variations in marine microbial biodiversity and function with inorganic nutrient loading, a large‐scale mesocosm (1,000 L) experiment was conducted in southern KCW for 10 days in summer (July 27 through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 91 publications
1
10
0
Order By: Relevance
“…By contrast, the abundance of certain Betaproteobacteria decreased due to competition for ammonium with phytoplankton (Christman et al, 2011). As a result, changes in phytoplankton abundance can influence variations in the phycosphere bacterial communities (Park et al, 2020), which is consistent with the findings of our study. Under nitrogen limitation, algae reached stability earlier (96h and 144h, Figure 1A).…”
Section: Changes In the Bacterial Diversity Index And Communities Und...supporting
confidence: 93%
See 1 more Smart Citation
“…By contrast, the abundance of certain Betaproteobacteria decreased due to competition for ammonium with phytoplankton (Christman et al, 2011). As a result, changes in phytoplankton abundance can influence variations in the phycosphere bacterial communities (Park et al, 2020), which is consistent with the findings of our study. Under nitrogen limitation, algae reached stability earlier (96h and 144h, Figure 1A).…”
Section: Changes In the Bacterial Diversity Index And Communities Und...supporting
confidence: 93%
“…These bacteria include attached and free-living bacteria (Seymour et al, 2017). Park et al (2020) discovered that the significant increase in phytoplankton abundance might be a key cause of the increase in bacterial abundance and changes in the communities along the southern Korean coast. Phytoplankton can secrete metabolites to provide nutrients for the phycosphere bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoplankton is known to steer bacterial communities (Pinhassi et al ., 2004; Teeling et al ., 2016; Park et al ., 2020). Tang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplankton is known to steer bacterial communities (Pinhassi et al, 2004;Teeling et al, 2016;Park et al, 2020). Tang et al (2020) compared cultivations with live and powdered algae and showed that the algae actively modulated the rearing water communities and increased cultivation performance.…”
Section: Algal Population In the Rearing Water Steers The Bacterioplamentioning
confidence: 99%
“…Phytoplankton is known to steer bacterial communities (Pinhassi et al, 2004;Teeling et al, 2016;Park et al, 2020). Tang et al (2020) compared cultivations with live and powdered algae and showed that the algae actively modulated the rearing water microbiomes and increased cultivation performance.…”
Section: Algal Populations Steer the Bacterioplankton Dynamicsmentioning
confidence: 99%